Entrepreneurial framing: How category dynamics shape the effectiveness of linguistic frames - Taeuscher, Karl; Rothe, Hannes (Strategic Management Journal, 2024)
Abstract Research Summary How do new entrepreneurial ventures effectively deploy linguistic frames to attract customer demand? Drawing on framing and categories research, we develop and test theory about how category dynamics shape the effectiveness of two commonly observed frames—social impact framing and innovativeness framing—in the context of prosocial categories. We test our predictions by tracking entrepreneurial ventures in the market category for massive open online courses over the category's first 10 years of existence (2012–2021). Our fixed‐effects models show that higher levels of category salience increase the effectiveness of a social impact framing but decrease the effectiveness of an innovativeness framing; conversely, higher levels of category crowdedness decrease the effectiveness of a social impact framing but increase the effectiveness of an innovativeness framing. Managerial Summary This research explores how startups can strategically frame themselves to attract customers. We specifically compare the effectiveness of a “social impact framing” (emphasizing the startup's benefits to society) versus an “innovativeness framing” (emphasizing innovativeness) under different market conditions. Our longitudinal study finds that startups benefit most from a social impact framing when their market attracts a lot of attention or has low competition. While an innovativeness framing can backfire under such conditions, it effectively helps to attract customers in a market that receives little attention or exhibits fierce competition. Entrepreneurs and managers can leverage our insights to more effectively tailor their framing strategies to their market environment and ultimately gain more customer traction.